"Making Medicine" with Salvia divinorum: Competing Approaches and Their Implications. Issue 7 (2nd October 2020) - Faudree, Paja
ABSTRACT: The psychoactive plant Salvia divinorum has long been used medicinally by Indigenous people from southern Mexico, the only place where it is endemic, and is now studied by pharmaceutical researchers. I analyze competing ways the two groups "make medicine" with salvia, attending simultaneously to material/embodied and semiotic/linguistic dimensions of those practices. I introduce two concepts – stripping and enrobing – to show that differences in how the groups interact with salvia have ethical and political consequences. Those repercussions matter because salvia is but one of many plants important to marginalized groups whose ties to them are threatened by international medical interests.